Metode Indikator Stabilitas Pada Penetapan Kadar Vitamin C Menggunakan Spektrofotometri Uv-Vis Dengan Degradasi Paksa Berupa Fotolisis - Fernanda, M.A. Hanny; Kamaliyah, Muhimmatul (Universitas Bhakti Kencana, 2022)
Ascorbic acid as an antioxidant and for endurance, especially during the covid – 19 season. Due to high demand, ascorbic acid manufactures are increasing their production. With the production of ascorbic acid, it is necessary to prepare a large stock of ascorbic acid in the factory. For that we need a method that can be used for ascorbid acid if degradation occurs during the storage period, especially due to photolysis. The study was conducted on samples of ascorbic acid with concentrations of 8, 10, and 12 ppm which were replicated 3 times. From the results of the absorbance value can be calculated the value of %RSD, correlation coefficient, and %Recovery. In this case, the value of %RSD = 2,0% (8 ppm); 1,7% (10 ppm); 0,5% (12 ppm); r = 0.9894; and %Recovery = 105% (8 ppm); 925 (10 ppm); 101% (12 ppm) which is in accordance with the acceptance criteria, namely %RSD = <2; r = 0.995; and %Recovery = 90-107%. Therefore, the UV spectrophotometry method can be carried out on ascorbic acid that has undergone photolysis degradation. In this case, the research results are still not perfect, so it is necessary to deepen the material on photolytically degraded ascorbic acid.